دور الجمعيات الخيرية في تحقيق التكافل الأجتماعي في ظل جائحة كورونا - جمعية دروب الخير ولاية الوادي -نموذجا- حسين نتيش بابه وفاء - ميسة, راضية; بابه, وفاء (University of Eloued-جامعة الوادي, 2022)
"تهدف هذه الدراسة إلى معرفة ""دور الجمعيات الخيرية في تحقيق التكافل الإجتماعي في ظل جائحة كور ونا جمعية دروب الخير نموذجا ""وهي إحدى الجمعيات الخيرية بولاية الوادي وانطلاقا من الإشكالية تدور حول طبيعة الدور الذي لعبته هذه الجمعية الخيرية والإجابة على التساؤلات المطروحة للوصول إلى أهداف ونتائج مضبوطة ودقيقة تسمح لنا بمعالجة موضوع دراسة، وقد أظهرت الدراسة عدة نتائج أهمها: -إن الجمعيات الخيرية تساهم في قيام المجتمعات واستقرارها ونموها لمستوى مرموق، حيث تقدم مساعدات مالية ومعنوية للمحتاجين وذلك الأصل في الجمعيات الخيرية هي الخدمة المجتمعية بدون هدف الربح. -التكافل الاجتماعي يساهم في استقرار المجتمع وتربطه وفي ظل الظروف وباء حثنا على تقديم المساعدات المادية والتي تأثرت وتأذت بفعل جائحة كورونا. -قد أجريت هذه الدراسة على عينة قصدية شملت 38 عائلة مستفيدة من الجمعية ولتحقيق أهداف اعتمدنا على المنهج الوصفي التحليلي الملائم لطبيعة هذه الدراسة معتمدين في جمع بيانات ،على كل من الملاحظة والمقابلة واستبانه مكونة من 6 أسئلة رئيسية تفرعت عنها أسئلة ثانوية وأتممنا بخاتمة تظم نتائج وتوصيات تتلخص في أن جمعية دروب الخير تعتبر من أهم الجمعيات الخيرية بالمنطقة لما تقدمه من مساعدة للفئات المعوزة والعائلات المحتاجة وإغاثة الملهوفين وهي رائدة في العمل الخيري والدور الذي لعبته في إرساء مبدأ التكافل الاجتماعي بين أفراد المجتمع في ظل الجائحة وتوصلنا إلى أنه من الضرورة تقديم الدعم لهذه الجمعيات الخيرية وإنشاء جمعيات أخرى ليعم الخير والتكافل بين أفراد المجتمع الواحد.""This study aimed to know “the role of charities in achieving social solidarity in light of the Corona pandemic ، the Paths of Good Association as a model”، which is one of the charities in the state of the valley، and based on the problem revolves around the nature of what this charity played and answering the questions raised to reach goals and results Accurate and accurate that allows us to address the subject of a study، and the study showed several results، the most important of which are: Charitable societies contribute to the establishment، stability and growth of societies to a prestigious level، as they provide financial and moral assistance to the needy، and that the origin of charities is community service without the goal of profit. Social solidarity contributes to the stability of society and links it، and in light of the pandemic conditions، we have urged us to provide material assistance، which has been affected and harmed by the Corona pandemic. This study was conducted on an intentional sample that included 38 families benefiting from the association. To achieve the objectives of this study، we relied on the descriptive analytical approach appropriate to the nature of this study. In collecting the data of this study، it was based on observation، interview، and a questionnaire consisting of 6 main questions that branched from secondary questions. I concluded with a conclusion that includes results and recommendations that are summed up in the fact that the Path of Goodness Association is one of the most important charitable associations in the region because of its assistance to needy groups and families in need and to seducing the desperate. It is a pioneer in charitable work and the role it played in establishing the principle of social solidarity among members of society in light of the pandemic Providing support to these charities and establishing other associations to spread goodness and solidarity among members of the same community."
مذكرة ماستر
Keywords: الجمعيات الخيرية -التكافل الاجتماعي -جمعية دروب الخير، جائحة كورونا; charities - social solidarity - paths of goodness association، corona pandemic